Vitreous hemorrhage: How important is role of radiological evaluation? A Case report - Sharma, Rohit; Singh, Tanu; Mishra, Dhiraj; Nargotra, Natasha; Sharma, Shashi; Bhutani, Abhivind; Rao, Dashrath; Sharma, Bharat Bhushan (Indian Journal of Case Reports, 2020)
Vitreous hemorrhage (VH) is most commonly caused by ocular trauma and proliferative diabetic retinopathy. Ultrasound is a very useful and effective modality in the diagnosis of VH. Sonography also helps in diagnosing the pathology of surrounding structures around the posterior chamber. This also helps in delineating the retinal anatomy. The opaque posterior chamber can easily be assessed by this modality. We present the case of a 15-year-old boy who reported with the left eye trauma 3 months back. He had initial redness and discharge followed by gradual loss of vision. He underwent sonographic evaluation of the left eye and was found to be having VH. He was advised surgical intervention by vitrectomy because of the chronicity of the problem. Ultrasonography of the eye is a very useful and effective tool for quick and hassle-free diagnosis of VH. This helps in fast management and can be useful in the salvage of some parts of the eye and subsequently vision. Medical and surgical contemplation can be carried out as per the sonographic findings.